“I prefer to get coronavirus than to stop working”: the street vendor’s perspective - Josuel Delgado-Enciso; Marina Delgado-Machuca; Karen A Mokay-Ramírez; Carlos E Barajas-Saucedo; Jessica C Romero-Michel; Mercedes Fuentes-Murguia; Nomely S Aurelien-Cabezas; Daniel Tiburcio-Jimenez; Jose A Toscano-Velazquez; Carmen Meza-Robles; Alejandra E Hernandez-Rangel; Mireya Walle-Guillen; et al. (Journal of Infection in Developing Countries)
During phase 2 of the COVID-19 pandemic in a Mexican City, informal street vendors (cases) and formal employees (controls) were interviewed. A total of 82.6% of street vendors preferred to expose themselves to the coronavirus than to stop working, compared with 18.4% of formal employees (adjusted OR = 19.4, 95%CI: 4.6-81.7, p < 0.001). Street vendors had 7 times less fear of dying from coronavirus (adjusted OR = 0.14, 95% CI: 0.03-0.5, p = 0.005) and showed a 16-times greater lack of real concern for the increase in cases in their community than the formal employees (adjusted OR = 0.06, 95% CI: 0.01-0.3, p = 0.002). Street vendors were the group with the poorest adherence to household and work area containment measures that continued to be in contact with others. The corresponding authorities must plan specific strategies that allow street vendors to survive economically, while at the same time, protecting community health.